Internal marketing and employee commitment in the hospitality industry. - Dr. Mahama Braimah (African Journal of Hospitality, Tourism and Leisure, 2016)
Internal marketing has been posited as a tool that can positively influence employees‟ to consistently deliver quality service. Internal marketing has also been said to impact employee behaviour in diverse ways, including employee commitment to the organisation. However, not much is known about the impact of internal marketing on employee commitment in small hotels, especially in subSaharan Africa. Again, the dimensions of internal marketing are not commonly agreed. This study is therefore an attempt to determine internal marketing dimensions in the small hotel sector, and evaluate its impact on employee commitment. A structured questionnaire was used to collect data. Respondents were selected using simple random sampling technique and data analysed using exploratory factor analysis, scale reliability test and multiple regression analysis. The study established seven dimensions of internal marketing comprising, internal communication, staff development, information communication technology (ICT), fairness, empowerment, teamwork and motivation. Together, these internal marketing dimensions had 26 items which predicting over 62% of the variance in employee commitment. ICT was the most significant dimension impacting employee commitment, while motivation did not have a statistically significant impact on employee commitment.